TUNTUTAN GANTI RUGI PADA PERLUASAN KEWENANGAN PTUN (STUDI KASUS BANJIR JAKARTA DAN PALEMBANG) - Erna Ratnaningsih (Faculty of Law, Tanjungpura University, 2023)
AbstractOne of the characteristics of a rule of law state is the existence of a State Administrative Court (PTUN) which guarantees that the government does not act arbitrarily against their people. The decision-making organs of the state sometimes do not pay much attention to the general principles of good governance and the applicable laws which result in losses for the community. To guarantee the rights of citizens, there is an extension of PTUN's authority. The type of research used is normative juridical research. The formulation of the problem in this paper is the extension of the authority of the Administrative Court and its implication to the community rights. It also creates obstacles to get justice because there is no clear mechanism in implementing the demands compensation for tort (PMH) by Government. Therefore, people can only sue but do not get actual compensation. The findings in this study regarding the decisions of flood cases in Jakarta and Banjarmasin are that there are injustice in demanding compensation. To ensure legal certainty and protection of the community, the extension of PTUN's authority must stipulate complete provision regarding the tort compensation mechanism, compensating for factual losses experienced by the community by the House of Representative in the amendment to Law Number 5 of 1986 concerning PTUN.AbstrakSalah satu ciri dari negara hukum adalah adanya Peradilan Tata Usaha Negara (PTUN) yang menjamin agar pemerintah tidak bertindak sewenang-wenang terhadap rakyatnya. Sering kali pengambilan keputusan organ negara tidak memperhatikan asas-asas umum pemerintahan yang baik dan peraturan perundang-undangan yang berlaku yang mengakibatkan kerugian bagi masyarakat. Untuk menjamin hak-hak warga negara maka terdapat perluasan kewenangan PTUN. Jenis penelitian yang digunakan adalah penelitian hukum yuridis normatif. Rumusan masalah dalam makalah ini adalah perluasan kewenangan PTUN dan implikasinya terhadap hak-hak warga negara. Perubahan ini berdampak pada adanya hambatan dalam mendapatkan keadilan karena belum adanya mekanisme yang jelas dalam pelaksanaan atas tuntutan ganti kerugian. Sehingga masyarakat hanya dapat menuntut namun tidak mendapatkan ganti kerugian aktual yang dideritanya. Adapun temuan dalam penelitian ini terhadap putusan kasus banjir di Jakarta dan Banjarmasin adalah adanya ketidakadilan dalam menuntut ganti kerugian pada perluasan kewenangan PTUN. Untuk menjamin kepastian hukum dan perlindungan masyarakat maka perluasan kewenangan PTUN harus mengatur ketentuan lengkap tentang mekanisme ganti kerugian PMH, mengganti kerugian faktual yang dialami oleh masyarakat oleh Pemerintah dalam perubahan UU Nomor 5 Tahun 1986 tentang PTUN.